ANALISIS PENGARUH PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN NASABAH MELAKUKAN PEMBIAYAAN PROGRAM REPLANTING KELAPA SAWIT (STUDI KASUS NASABAH BANK RIAU KEPRI SYARIAH KCP LIPATKAIN) - Sukwan Efendi; Amsah Hendri Doni (Adisam Publisher, 2025)
Several types of financing products at Bank Riau Kepri Syariah KCP Lipatkain, one of which is financing for the oil palm replanting program. To improve customer decisions in financing the oil palm replanting program at Bank Riau Kepri Syariah KCP Lipatkain, there is a need for product marketing, prices and promotions. This research aims to determine and analyze: (1) The influence of products on customer decisions (2) The influence of price on customer decisions (3) The influence of promotions on customer decisions (4) The influence of products, prices and promotions on customer decisions simultaneously. This research is field research using descriptive quantitative methods. The sample in this study was 58 customers who were used as respondents, the collection method was based on the Non Probability Sampling method or saturated sampling where the entire population was selected as a sample, namely 58 customers of Bank Riau Kepri Syariah KCP Lipatkain for the 2023 oil palm replanting program. The data collection technique used questionnaires and observations. The data analysis techniques used in this research were research instrument tests (validity test and reliability test), classical assumption tests (autocorrelation test, normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression test, R2 determinant coefficient test, and hypothesis testing (T test) and (F test). Based on the results obtained in this research, the product variable obtained results with a significant value greater than alpha 0.05% (0.348 ≥ 0.05), the price variable obtained results with a significant value smaller than alpha 0.05% (0.000 ≤ 0.05), the promotion variable obtained results with a significant value greater than alpha 0.05% (0.721 ≥ 0.05). Based on the results of research tests using multiple linear analysis techniques, it can be stated simultaneously or together that there is a positive and significant influence with a significant F value of 0.000 ≤ 0.05. The determinant coefficient (R2) value is 0.377 or 37.7%, which means that simultaneously there is a contribution from the independent variable to the dependent variable of 0.377 or 37.7% and the remaining 62.3% is influenced by other variables not discussed in this research, namely variables location, services, procedures and facilities.